Maximizing The Benefits Of Corporate Social Responsibility. How Companies Can Derive Benefits From Corporate Social Responsibility - Michel, Nora; Buler, Stephen A. (European Scientific Journal, ESJ, 2016)
Corporate Social Responsibility can be used as a business strategy by firms to improve many different areas of their business. Research has shown that, if implemented correctly, the benefits of CSR tend to outweigh the costs.